SIRT4 and Its Roles in Energy and Redox Metabolism in Health, Disease and During Exercise - Han, Yumei; Zhou, Shi; Coetzee, Sonja; Chen, Anping (Frontiers in Physiology, 2019)
NAD+-dependent SIRT4 has been reported to be a key regulator of metabolic enzymes and antioxidative defence mechanisms in mitochondria. It also plays an important role in regulation of mitochondrial metabolism in response to exercise. Recent studies have shown that SIRT4 is involved in a wide range of mitochondrial metabolic processes, including depressing insulin secretion in pancreatic beta cells, promoting lipid synthesis, regulating mitochondrial ATP homeostasis, controlling of apoptosis, and regulating redox. SIRT4 also appears to have complex enzymatic functions and is involved in ADP-ribosylation, lysine deacetylation and lipoamidation. However, the effects of metabolic diseases and changes in metabolic homeostasis such as during exercise on SIRT4, and the roles of SIRT4 in regulation of metabolic function in response to diseases and exercise are not well understood. The aim of this narrative review was to summarise the current research on the significance of the SIRT4 as a metabolic regulator and mitochondrial function, and its putative roles in relation to metabolic diseases and exercise.